2024
DOI: 10.3389/fnint.2024.1379208
|View full text |Cite
|
Sign up to set email alerts
|

Auditory feedback decreases timing variability for discontinuous and continuous motor tasks in autistic adults

Nicole Richard Williams,
Luc Tremblay,
Corene Hurt-Thaut
et al.

Abstract: IntroductionAutistic individuals demonstrate greater variability and timing error in their motor performance than neurotypical individuals, likely due at least in part to atypical cerebellar characteristics and connectivity. These motor difficulties may differentially affect discrete as opposed to continuous movements in autistic individuals. Augmented auditory feedback has the potential to aid motor timing and variability due to intact auditory-motor pathways in autism and high sensitivity in autistic individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…The researchers proposed that the interactive sonification (i.e., notes changing with movement) engaged children in motor movement training, helping them to complete more accurate movements and improve attention to the exercises. Similarly, Richard Williams et al (2024b) found that autistic adults has less motor variability when completing a discontinuous and continuous drawing task with the presence of auditory feedback. These studies indicate that auditory and sonified feedback may help promote movement and decrease the variability of movements in autistic individuals.…”
Section: Rhythm and Music For Sensorimotor Developmentmentioning
confidence: 85%
“…The researchers proposed that the interactive sonification (i.e., notes changing with movement) engaged children in motor movement training, helping them to complete more accurate movements and improve attention to the exercises. Similarly, Richard Williams et al (2024b) found that autistic adults has less motor variability when completing a discontinuous and continuous drawing task with the presence of auditory feedback. These studies indicate that auditory and sonified feedback may help promote movement and decrease the variability of movements in autistic individuals.…”
Section: Rhythm and Music For Sensorimotor Developmentmentioning
confidence: 85%